Comparative Biochemical Study of Interleukin -35 and Some Sex Hormones in MS Female Patients with Duration of the Disease* - Baden, Ali K.; Ali, Bushra H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Multiple sclerosis (MS) is a chronic disorder of the central nervous system (CNS) characterized by autoimmune inflammation, demyelination, and axonal damage. The present study aimed to shed a light on the contribution of interlukin-35 and its relation to some sex hormones in the pathogenesis of multiple sclerosis. Sixty six female patients with age range (20-40) years were taken from Baghdad Teaching Hospital through the period from Nov. 2012 to –April 2013 and 20 apparently healthy subject as control group matched age as group G1. The patients were divided into three groups depending on duration of MS diseases G2 from 3 months to 2 years, G3 from 2 years to 4 years, G4 from 4 years to 10 years and more. Investigations included estimation of serum levels of Interlukin-35 (IL-35), Testosterone (TEST), Progesterone (PROG), follicle stimulating hormone (FSH), luteinizing hormone (LH) and Prolactin (PRL). Serum IL-35 levels were significantly higher in MS patients as compared with control subject, also significant increase appeared in TEST levels in G3 compared to control in for MS female patients. No significant differences were found between PROG and FSH with duration also non-significant difference levels G2 compared to G1 in LH, on the other hand a significant increase levels for LH in G3 and G4 compared to control subject , a significant difference in prolactin levels for G2 and G4, but non-significant difference for G3. From this study a conclusion was drawn, that evaluation of concentration of a new super family cytokines IL-35 can be considered as a clinical biomarker in multiple sclerosis female patients. This finding may indicate that MS might influence cytokine e.g. interleukin-35 production in these patients.